Formulasi Sediaan Lotion Dari Ekstrak Buah Alpukat (Persea Americana) dan Lidah Buaya (Aloe Vera) Untuk Kulit Kering - Marlia Oktaviana; Dwi Putri Rejeki; Ria Ceriana; Rosa Mardiana; Sasmiati Farach Dita (Forum Kerjasama Pendidikan Tinggi (FKPT), 2021)
Skin care is needed so that the skin does not become dry, rough, and dull. The way to deal with dry skin is to use a scrub or use a moisturizer such as lotion. One of the active substances contained in lotion preparations is antioxidant compounds. Avocado and aloe vera extracts have antioxidant activity. Avocado and aloe vera have moisturizing benefits. In this study, both types of extracts were formulated into lotion preparations. Avocado and aloe vera extracts were made by maceration method using 70% ethanol as solvent. The extract was formulated with 3 variations, namely the control formula (F0), the avocado extract formula with a concentration of 5% (FI), and aloe vera with a concentration of 10% (F II). The lotion was tested for physical properties including pH, homogeneity, stability, spreadability and irritation tests. The results showed that the lotion containing avocado and aloe vera extracts with storage for two weeks was stable. Does not change shape, smell, color, and does not irritate the skin